Intranasal administration of ghrelin receptor antagonist [D-Lys-3]-GHRP-6 reduces the manifestations of impulsivity and compulsivity induced by maternal deprivation in rats - Sarng S. Pyurvee; Andrei A. Lebedev; Eugeny R. Bychkov; Petr D. Shabanov (Belgorod National Research University, 2024)
Introduction: The aim of our study was to investigate the effects of ghrelin receptor antagonist [D-Lys-3]-GHRP-6 on impulsivity and compulsivity in a model of gambling addiction in adult rats after maternal deprivation MD in early ontogenesis. Materials and Methods: The cubs were deprived of their mother daily for 3 h from days 2 to 12 postnatal. Adult Wistar rats were trained in a three-arm maze for 21 days. Two seeds were fed in arm 1 with reinforcement mode FR1. In arm 2, three seeds were presented with reinforcement mode FR2; in arms 3, 4 seeds were presented with reinforcement mode FR3 (i.e., only every 3rdrun to the feeder was reinforced with food). The animals were also examined to quantify their status of compulsive behavior in a marble test. The rat was placed in the cage with sawdust and glass beads for 30 min, after which, the number of balls covered with sawdust by more than 2/3 was counted. Results: In the MD group, the number of entrances to arm 3 increased 1.5-fold, indicating the selection of a larger reinforcement value at its low probability. The number of entrances to arm 1 (reward with high probability (100%) but with the lowest food reinforcement) decreased compared to the control group. The intranasal administration of the selective GHSR1A receptor antagonist [D-Lys (3)]-GHRP-6 (1 mg/mL) to animals MD led to significant (p<0.01) increase in the number of visits to arm 1. Additionally, there was a tendency to decrease the number of buried balls in rats treated with [D-Lys (3)]-GHRP-6. Conclusion: Thus, the work shows that chronic stress of MD causes a behavioral strategy in animals aimed at obtaining more significant food reinforcement, but with a low probability of achieving it, which is associated with an increase in the impulsive component of gambling addiction. MD also causes an increase in the number of buried balls in the marble test, which is associated with an increase in the compulsive component of gambling addiction. Intranasal administration of GHS-R1a antagonist [D-Lys (3)]-GHRP-6 to rats MD significantly reduces increased impulsive activity in Iowa test. The data obtained in rats MD opens up the possibility of creating drugs targeted at ghrelin receptors. The intranasal method of administering peptide substances used in the work substantiates the possibility of using this method of administration.